Jatrowedione, a lathyrane diterpene from Jatropha weddelliana - Brum, R. L.; Honda, N. K.; Mazarin, S. M.; Hess, S. C.; Cavalheiro, Alberto José [UNESP]; Delle Monache, F. (Elsevier B.V., 1998)
3-Acetylaleuritolic acid, sitosterol and a novel lathyrane diterpene, jatrowedione, have been isolated from the roots of Jatropha weddelliana. The elucidation of the structure of the latter was accomplished by detailed NMR investigation, and the relative configuration was established by difference NOE experiments. (C) 1998 Published by Elsevier B.V. Ltd. All rights reserved.
Keywords: Jatropha weddelliana; Euphorbiaceae; diterpene; lathyrane; jatrowedione; pantanal